Identification of lurasidone as a potent inhibitor of severe fever with thrombocytopenia syndrome virus by targeting the viral nucleoprotein - Ting Cheng; Qingcui Xiao; Jing Cui; Shuangjie Dong; Yuqin Wu; Wenqiang Li; Xinya Yang; Lina Ma; Zhiyong Li; Zhiyong Li; Zhiyong Li; Peng Sun; et al. (Frontiers in Microbiology)
IntroductionSevere fever with thrombocytopenia syndrome virus (SFTSV) is an emerging tick-borne bunyavirus that causes acute febrile illness with thrombocytopenia and a high mortality rate in humans. Currently, no specific antiviral agents have been approved for the prevention or treatment of SFTSV infection. The viral nucleoprotein (NP) is a critical component involved in viral RNA replication and transcription, representing a promising target for antiviral drug development.MethodsWe performed a structure-based virtual screening of the FDA-approved drug library using AutoDock Vina, aiming to identify potential inhibitors targeting the RNA-binding pocket of SFTSV NP. Promising candidates were further evaluated for antiviral activity in vitro.ResultsAmong the screened compounds, lurasidone exhibited strong antiviral activity against SFTSV, with an IC50 value of 4.552 μM and a selectivity index (SI) greater than 10, indicating favorable antiviral potency and low cytotoxicity. Mechanistic investigations suggest that lurasidone may exert its inhibitory effect by directly binding to the NP, thereby interfering with viral genome replication.ConclusionThis study identifies lurasidone as a potential antiviral candidate targeting SFTSV NP and provides a theoretical basis for the repurposing of FDA-approved drugs against emerging viral infections. These findings offer new insights into therapeutic strategies for the treatment of SFTSV.